The Effectiveness of Steam-Based Contextual Teaching and Learning (CTL) Models on High School Students' Logical Thinking Ability in Science Learning - Ulum, Moh Miftakhul; Khotimah, Khusnul; Elfiana, Dwi Endah (Spectrum of Science Education Research and Application, 2024)
Science learning is an educational approach that involves material related to everyday life, where the skill of logical thinking is crucial as a criterion for determining the success or failure of the learning process. The shift from online to offline learning systems in high schools has generally led to a decline in students' logical thinking skills in the field of science education. Therefore, the implementation of Contextual Teaching and Learning (CTL) methodology based on STEAM is an effort to enhance learning. This is because this methodology can help high school students understand subjects by establishing connections between the subjects and everyday life, thereby supporting student activities. This study was conducted to determine how high school students engage in academic activities and to assess the effectiveness of the CTL methodology based on STEAM on students' logical thinking skills. This research is a quantitative study, specifically a quasi-experimental design with a non-equivalent control group design. In addition to activity sheets and student performance, the learning instruments also included questions that assessed participants' logical thinking skills. T-tests and N-Gain were used in the analysis of the study. The results showed that the learning and student activities were successfully carried out with a "good" category. Furthermore, based on the t-test results, it can be concluded that H0 is rejected while H1 is accepted. This indicates that there is a difference in logical reasoning abilities between the experimental group and the control group. According to the average N-Gain test results, the experimental group scored higher than the control group, with an average of 57.2496, indicating that the CTL methodology based on STEAM had a significant and effective impact on enhancing high school students' logical thinking skills